Rāingān chabap sombūn Khrōngkān sưksā ph̄ưa yokrāng kotmāi wādūai kānčhatkān kh̨ōng sīa ʻantarāi - Direk Patamasiriwat (Sathāban Wičhai Sangkhom, Mahāwitthayālai Chīang Mai, 2004)
Feasibility study on pollution control and hazardous waste management in order to propose amendment to the related laws in Thailand.